Non-isothermal cure and exfoliation of tri-functional epoxy-clay nanocomposites - F. Shiravand; J. M. Hutchinson; Y. Calventus (eXPRESS Polymer Letters, 2015)
The non-isothermal cure kinetics of polymer silicate layered nanocomposites based on a tri-functional epoxy resin has been investigated by differential scanning calorimetry. From an analysis of the kinetics as a function of the clay content, it can be concluded that the non-isothermal cure reaction can be considered to consist of four different processes: the reaction of epoxy groups with the diamine curing agent; an intra-gallery homopolymerisation reaction which occurs concurrently with the epoxy-amine reaction; and two extra-gallery homopolymerisation reactions, catalysed by the onium ion of the organically modified clay and by the tertiary amines resulting from the epoxy-amine reaction. The final nanostructure displays a similar quality of exfoliation as that observed for the isothermal cure of the same nanocomposite system. This implies that the intra-gallery reaction, which is responsible for the exfoliation, is not significantly inhibited by the extra-gallery epoxy-amine cross-linking reaction.